Efficacy and Safety of Chinese Patent Medicine for the Prevention and Treatment of Radiotherapy and Chemotherapy-Induced Oral Mucositis: A Systematic Review and Meta-Analysis - Xie, Yufei; Fang, Xin; Hua, Hong; Zhou, Peiru (Frontiers in Pharmacology, 2022)
Background: Radiotherapy and chemotherapy-induced oral mucositis can affect cancer patients’ quality of life, even necessitate cancer therapy and influence prognosis. Chinese patent medicines (CPMs) have been widely used as complementary alternative medicines for the prevention and treatment of oral mucositis, and their efficacy and safety require further evaluation. Therefore, this study was conducted to provide references for clinical practice. Methods: Ten databases were searched electronically and manually to identify randomized controlled trials (RCTs) from their inception to August 2021, concerning the prevention and treatment of radiotherapy and chemotherapy-induced oral mucositis with CPMs. The prevalence, pain level, and the severity of radiotherapy and chemotherapy-induced oral mucositis, as well as the effectiveness rate and adverse effects of CPMs, were set as the outcome criteria. The assessment criteria of the Cochrane Handbook were used to determine study quality and bias, and meta-analysis was conducted using Review Manager 5.4.1 software. Results: A total of 2,312 cases from 27 RCTs were included. Most studies were considered to have a low or unclear risk of bias. More research is available on the use of CPMs in the prevention of radiotherapy and chemotherapy-induced oral mucositis than in its treatment. As for the prevention, it was proved that CPMs could significantly reduce the prevalence of radiotherapy and chemotherapy-induced oral mucositis, especially for the severe types, and decrease pain levels (p < 0.05). For treatment, CPMs could alleviate the symptoms, promote the healing of ulceration in radiotherapy and chemotherapy-induced oral mucositis, and thus improve the efficiency of clinical treatment (p < 0.05). The results of subgroup analyses were mainly consistent with the above results. The adverse effects of CPMs mainly included gastrointestinal reactions and bitter taste, and no serious adverse events were reported. Conclusions: This systematic review and meta-analysis indicated CPMs might be effective for the prevention and treatment of radiotherapy and chemotherapy-induced oral mucositis through reducing the prevalence, decreasing the occurrence of severe types, alleviating the symptoms, and promoting the healing of ulceration. However, due to the limited number of eligible studies and the publication bias, more high-quality, double-blinded, placebo-controlled RCTs are still needed in future research. Systematic Review Registration: [https://inplasy.com/], identifier [INPLASY2021100100].